The significance of αβ Т cells in the development of metainflammation of the adipose tissue in obesity - A.E. Abaturov; A.O. Nikulina (Zaslavsky O.Yu., 2021)
The literature review presents modern ideas about the role of αβ T cells, which are represented by the main groups: CD4+, CD8+ T lymphocytes and double-negative CD4-CD8- T and double-positive CD4+CD8+ T cells of the adaptive immune system of the organism in the development of metainflammation of adipose tissue in obesity. According to the modern concept, obesity is associated with adipocyte hypertrophy, impaired adipogenesis, the development of metainflammation of adipose tissue that in the early adaptive phase is characterized by the rapid reactivation of memory T cells. The physical connection of cells performing the function of energy storage with immunological memory cells is a special mechanism for the body's survival during periods of nutritional deficiency. Excess adipose tissue and the appearance of pro-inflammatory hypertrophied adipocytes change the spectrum and ratio of produced adipokines and cytokines, which leads to the recruitment and activation of pro-inflammatory immunocytes and depletion of the pool of anti-inflammatory cells of the innate and adaptive immune system in adipose tissue. Changes in the representation of resident recruited immune cells in adipose tissue during obesity is characterized by the accumulation of pro-inflammatory cells (neutrophils, M1 Mϕ, mast cells, NK, Th1, Th17, Th22 cells) and depletion of regulatory and anti-inflammatory populations (eosinophils, M2 Mϕ, ILC2, iNKT, γδ T, Th2, Treg, B1 cells). Excessive production of interferon γ and tumor necrosis factor α leads to the development of insulin resistance, and interleukin 17 - to degradation of the extracellular matrix of adipose tissue and impaired adipogenesis. In obesity, CD8+ T cells and M1 Mϕ macrophages eliminate hypertrophied adipocytes. A decrease in the activity of Treg cells increases the pro-inflammatory potential of adipose tissue. Despite the progress achieved in disclosing the role of the adaptive immune system in the development of obesity, the antigens associated with adipose tissue, the mechanisms of their generation have not been identified so far, the role of most tissue-specific alarmins has not been determined; the mechanisms that determine the timing, sequence and activity of recruitment of various types of immunocytes are not known. The data of modern studies on the immunopathogenesis of metainflammation of adipose tissue and the creation of drugs that will improve the efficiency and individualize anti-inflammatory therapy in obese patients are presented.